Quality of Life in Women with Gynecological Cancers: A Study in Tertiary Care Hospital of Pakistan - Dahar, FalakNaz Naz; Chishti, Uzma; Amir Ali, Fouzia; Khan, Rozilla Sadia; Ali, Nasir; Raza, Amir; Aziz, Aliya B (Asian Pacific Journal of Cancer Care, 2024)
Background: Patient survival has been improved in gynecological cancer due to recent advances in diagnosis and treatment modalities. However longer survival time makes quality of life an even more challenging aspect of care. The aim of study was cross sectional evaluation of the quality of life in Gynecological cancer survivors completing at least 5 years of follow-up after treatment. Materials and Methods: In this prospective, single-center study, 162 women were interviewed at least 3 months after completion of treatment and no longer than 5 years. Data was collected on validated questionnaire i.e. EORTC QLQ-C30 from all participants & specific questionnaires specific to cancers i.e. OV28, CX24 & EN24. Results: The study population comprised of 25 (15.4%), 82 (50.6%) and 55 (34%) women with Cervical, endometrial, and Ovarian cancer, respectively. Average Quality of life was found to be 77.93±16.65. Mean Quality of life was reported as 74.67 in cervical cancer, 77.34 in endometrial cancer & 80.30 in ovarian cancer respectively. Similarly, five functional scales like physical (PF), role (RF), emotional (EF), cognitive (CF) and social (SF) were estimated within the mean range of 80 to 90. Fatigue & insomnia were the most common symptoms reported. Sexual functioning was the main concern among patients included in the study. Other than that, musculoskeletal pain and lymphedema were the main issues reported by patients of endometrial cancer. Conclusion: Study Participants showed overall a good quality of life. However, certain concerns related to sexual quality of life, and chronic lymphedema need special attention to improve quality of care.